Risk Management Techniques and Insurance Buying Behaviour: Evidence from Small and Medium-Sized Enterprises in Lagos, Nigeria: Array - Ajemunigbohun, Sunday (Acta Universitatis Danubius. Œconomica, 2022)
Risk management techniques are important metrics in safeguarding the lives and property of mankind. They influence the behavioural attitude of people to perceive the image of insurance as an intangible, inseparable, variable, and transferable product. Therefore, this study aimed at assessing the effects of risk management techniques on insurance buying behaviour, with specific reference to the perceptions of selected SMEs in Lagos, Nigeria. The study adopted a cross- sectional survey research design. The study population consisted of the total number of registered SMEs recorded in Lagos State at 11,666. Thus, a single-stage cluster sampling technique was employed in the questionnaire distribution and data collection processes. Two hundred and forty-three (243) respondents were used in the study. The statistical technique employed was simple regression. This study confirms the importance of risk management techniques in the behavioural evaluation of insurance purchases in Lagos, Nigeria. It is recommended that insurance providers in Nigeria should attempt to tailor insurance products in a lovable and affordable manner to SMEs’ operators/owners in a bid to improve on their behavioural risk attitudes. More so, interest should be placed on impressive risk management communication and ideal risk financing techniques among SMEs’ owners/operators.